Plantago asiatica mosaic virus: An emerging plant virus causing necrosis in lilies and a new model RNA virus for molecular research - Komatsu, Ken; Hammond, John (Molecular plant pathology, 2022)
Taxonomy Plantago asiatica mosaic virus belongs to the genus Potexvirus in the family Alphaflexiviridae of the order Tymovirales. Virion and genome properties Plantago asiatica mosaic virus (PlAMV) has flexuous virions of approximately 490–530 nm in length and 10–15 nm in width. The genome of PlAMV consists of a single‐stranded, positive‐sense RNA of approximately 6.13 kb. It contains five open reading frames (ORFs 1–5), encoding a putative viral polymerase (RdRp), movement proteins (triple gene block proteins, TGBp1‐3), and coat protein (CP), respectively. Host range PlAMV has an exceptionally wide host range and has been isolated from various wild plants, including Plantago asiatica, Nandina domestica, Rehmannia glutinosa, and other weed plants. Experimentally PlAMV can infect many plant species including Nicotiana benthamiana and Arabidopsis thaliana. It also infects ornamental lilies and frequently causes severe necrotic symptoms. However, host range varies depending on isolates, which show significant biological diversity within the species. Genome diversity PlAMV can be separated into five clades based on phylogenetic analyses; nucleotide identities are significantly low between isolates in the different clades. Transmission PlAMV is not reported to be transmitted by biological vectors. Virions of PlAMV are quite stable and it can be transmitted efficiently by mechanical contact. Disease symptoms PlAMV causes red‐rusted systemic necrosis in ornamental lilies, but it shows much weaker, if any, symptoms in wild plants such as P. asiatica. Control Control of the disease caused by PlAMV is based mainly on rapid diagnosis and elimination of the infected bulbs or plants. This pathogen profile summarizes current knowledge regarding Plantago asiatica mosaic virus, including its host range, strain differentiation, host interactions, and utility as a viral vector to examine virus–host interactions.